Hayek-Myrdal interactions in the early 1930s: New facts change an old story - Lars Jonung; David E. W. Laidler (Lund University, School of Economics and Management, Department of Economics, 2025)
It is widely believed that Friedrich von Hayek's first encounter with Gunnar Myrdal involved the latter's last-minute contribution, as a replacement for Erik Lindahl, to a Sammelband edited by the former in 1933, and that Hayek was lukewarm towards Myrdal and his ideas from the very beginning. Correspondence between the two shows that, in fact Myrdal was among Hayek's original invitees, and that their relationship was co-operative and cordial for two years prior to the publication of this collection. We suggest that the content, and perhaps even more, the tone of Myrdal's paper, originally intended for the Journal of Political Economy, alienated Hayek, who nevertheless treated Myrdal's work with academic propriety thereafter. The origin of Myrdal's famous ex post - ex ante terminology is also revealed.
Keywords: B2; B3; E1; E2; E3; 330; Hayek; Myrdal; Stockholm School; ex ante - ex post